PADA PROSES PERNIKAHAN MASYARAKAT SUKU SASAK DALAM PERSPEKTIF ANTROPOLOGI HUKUM (STUDI DI DESA GONDANG, KABUPATEN LOMBOK UTARA) - Ahmad Gautsul Anam; Ach. Faisol; Syamsu Madyan (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2021)
Marriage is something that is very sacred in human life to unite two different people. Besides being believed to be sacred, marriage is a sunnah practice that is carried out in addition to carrying out descendants, it is also a form of worship. There are various kinds of traditions in the marriage process carried out in order to achieve the fabric of love and affection for the two people, that the marriage process is carried out with the demands of religious law and in a tradition that becomes a habit carried out by the local community in carrying out the marriage. The tradition is preserved and made a habit because it can become the identity of a region, and how the provisions of an area to overcome this. As with the marriage tradition found in North Lombok or Gondang Village in particular, that the tradition of returning home has various processes that are used as customs to obtain legal approval in accordance with applicable customary manners and cannot be separated from the guidance of Islamic teachings. So that a tradition can be preserved and made a habit in recognizing the identity of an area.